Value Chain of Gastronomic Tourism in Ubud, Bali - Ismayanti Istanto; Ina Djamhur (Conference Series, 2020)
Abstract. Gastronomic tourism as one form of sustainable tourism has not yet developed in Indonesia. Gastronomic tourism is a bridge between the past and the future to preserve food culture. In 2019, Ubud Bali is chosen to become a world-class gastronomic destination complied with UNWTO standard. The research aims to identify the elements of gastronomic tourism and gastronomic value chains as tourist attractions in Ubud, Bali. Focused discussion, interviews and observations are used to compile data and information then, descriptively analyzed. Research results show that gastronomic elements that can be used as tourist attractions in Ubud include food tours, visits to food producers, home cooking activities and home dining experience, cooking classes in restaurants, and events in traditional cuisine. These elements are interconnected in the value chain of gastronomic tourism, from upstream to downstream, from planting food to promotion and commercialization. The activities of gastronomy tourism in Ubud involves many forms of tourism, such as: agricultural tourism, organic tourism, educational tourism, historical tourism, and food tourism (cooking class).